ESG, dividend payout policy and the moderating role of audit quality: Empirical evidence from Western Europe - R. M. Ammar Zahid; Alina Taran; Muhammad Kaleem Khan; Ionela-Corina Chersan (Borsa İstanbul Review, 2023)
This study investigates the relationship between environmental, social, and governance (ESG) scores and dividend policies, considering the moderating role of audit quality. Based on data for Western European listed companies (leaders in ESG revolution) over the period 2010-2019, panel regression analyses show a significant positive relationship between ESG and dividend payouts. Thus, companies with strong ESG practices prove their stakeholders' and shareholders' orientation, maintaining their dividend payments. However, involvement in high-quality ESG practices slows dividend growth. Audit quality has also a negative moderating effect on ESG-dividend links, prevalent at the firms whose financial audit is conducted by Big Four auditors, with no statistically significant results for ESG assurance quality. The findings are robust to sensitivity analyses based on alternative measures and estimation techniques. These results have implications for investors, management, analysts, and policy makers, providing significant lessons for companies and markets concerned about extending their ESG policies.
Keywords: G35; M14; M42; 330; Audit quality; Dividend payout policy; ESG; Western Europe